2015
DOI: 10.1002/ps.4146
|View full text |Cite
|
Sign up to set email alerts
|

Impact of neonicotinoid seed treatment of cotton on the cotton leafhopper,Amrasca devastans(Hemiptera: Cicadellidae), and its natural enemies

Abstract: BACKGROUND Neonicotinoid seed treatments suppress populations of pest insects efficiently and can enhance crop growth, but they may have negative effects on beneficial arthropods. We evaluated the effects of either imidacloprid or thiamethoxam on the abundances of a sucking pest, the cotton leafhopper (Amrasca devastans), and its arthropod predators under field conditions. We also evaluated the impact of seed treatment on transgenic cotton plant growth, with pests and natural enemies present or absent. RESULTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 23 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…Similarly, in a field trail using seed treatment of cotton, thiamethoxam had a greater suppressive effect than imidacloprid on Orius sp. populations (Saeed et al, 2015). The effects of these neonicotinoids on other Orius spp.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a field trail using seed treatment of cotton, thiamethoxam had a greater suppressive effect than imidacloprid on Orius sp. populations (Saeed et al, 2015). The effects of these neonicotinoids on other Orius spp.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the sticky card data, visual counts of leafhoppers on plants were significantly higher in the insecticide treated plots. Since these sucking insects are susceptible to neonicotinoids, it is possible that they were sub‐lethally intoxicated, which could have reduced their mobility and increased the chances of being counted during visual plant inspections . Like thrips, leafhoppers rarely reach damaging levels on corn in the mid‐Atlantic US.…”
Section: Discussionmentioning
confidence: 99%
“…Since these sucking insects are susceptible to neonicotinoids, 58,60 it is possible that they were sub-lethally intoxicated, which could have reduced their mobility and increased the chances of being counted during visual plant inspections. 61 Like thrips, leafhoppers rarely reach damaging levels on corn in the mid-Atlantic US. Other herbivores, including corn leaf aphids, corn blotch leafminers, corn flea beetles, and several species of plant bugs, were significantly reduced by 28 to 55% in the clothianidin-seed treated plots.…”
Section: Impact On Herbivoresmentioning
confidence: 99%
“…Thus, cotton plants grown from seeds treated with thiamethoxam at the recommended doses (3 g/kg) reduced the populations of natural enemies of the cotton leafhopper by about 35%, in particular those of Chrysoperla sp., Orius sp., and spiders, whereas cotton plants grown from seeds treated with imidacloprid (5 g/kg) did not lead to significant reductions (i.e., < 10%) of the same species (Saeed et al 2016). Trials in South Dakota demonstrated the effectiveness of seed treatments of thiamethoxam and imidacloprid, whether alone or in combination with foliar sprays of beta-cyflutrin, for controlling aphids.…”
Section: Predatorsmentioning
confidence: 91%
“…However, it is important to note that sublethal effects were not evaluated in the study (Saeed et al 2016). Uhl et al (2015) studied trophic interactions in a threelevel food chain mesocosm: wild strawberry Fragaria vesca, wood cricket Nemobius sylvestris, and nursery web spider Pisaura mirabilis.…”
Section: Impacts On Natural Systems For Pest and Weed Controlmentioning
confidence: 99%